EXPERIENCE OF MODERN APPROACHES TO NATURAL WATER QUALITY ESTIMATION FOR THE PREDICTION OF TECHNOLOGICAL METHODS OF ITS CONDITIONING - Єзловецька, І. С. (WATER AND WATER PURIFICATION TECHNOLOGIES. SCIENTIFIC AND TECHNICAL NEWS, 2013)
The three basic approaches to estimation of water quality of drinking water supply according to hygienical and ecological criteria are grounded and used. The specific character of formation conditions of river waters quality is considered for chosen water objects. Their present state and degree of ecological prosperity according to integral indexes is estimated. Possibility of the usage of this water objects as potential sources for drinking water supply of rural population is established. The prediction necessity of water quality in the explored rivers basins is finded out depending on hydrological periods. The priority indexes of water quality, which are needed the application of the special technological decision are defined. The enumeration of modern natural water treatment methods is offered for contents correction of contaminating matters. The experience concerning of modern approaches use to estimation of natural water quality is presented in the paper. There is recommended for the creation of multistage technologies for drinking water treatment with usage of biological and physical methods to prevent the disinfection by-products formation.